Economics of agritourism development: An Iranian experience - Mohammad Hossein Askarpour; Amir Mohammadinejad; Reza Moghaddasi (Economic Journal of Emerging Markets, 2020)
Agritourism is known as a means of identification and realization of various on-farm and off-farm attractions existing in rural areas. This study aims at exploring the main determinants of agritourism development in Iran. Data were obtained via field survey and interview with 115 sample farmers from areas currently presenting agritourism services. By using a multinomial logit model, the impacts of theoretically expected variables were estimated. Findings/Originality:  Education is the main driver of agritourism development. The programs aiming at increasing the knowledge of farmers regarding different advantages of agritourism should be paid special attention by the government. The result also indicates direct effect of diversified crops and services on probability to get involved in agritourism business. Provision of more crops and services on the farm generates more attraction for tourists and can lead to development of agritourism. In addition, farm size revealed same association, while the age of farmers has an adverse effect on provision of agritourism.